Nonrotating Convective Self‐Aggregation in a Limited Area AGCM. (13th April 2018) - Arnold, Nathan P.; Putman, William M.
Abstract: We present nonrotating simulations with the Goddard Earth Observing System (GEOS) atmospheric general circulation model (AGCM) in a square limited area domain over uniform sea surface temperature. As in previous studies, convection spontaneously aggregates into humid clusters, driven by a combination of radiative and moisture‐convective feedbacks. The aggregation is qualitatively independent of resolution, with horizontal grid spacing from 3 to 110 km, with both explicit and parameterized deep convection. A budget for the spatial variance of column moist static energy suggests that longwave radiative and surface flux feedbacks help establish aggregation, while the shortwave feedback contributes to its maintenance. Mechanism‐denial experiments confirm that aggregation does not occur without interactive longwave radiation. Ice cloud radiative effects help support the humid convecting regions but are not essential for aggregation, while liquid clouds have a negligible effect. Removing the dependence of parameterized convection on tropospheric humidity reduces the intensity of aggregation but does not prevent the formation of dry regions. In domain sizes less than (5, 000 km) 2, the aggregation forms a single cluster, while larger domains develop multiple clusters. Larger domains initialized with a single large cluster are unable to maintain them, suggesting an upper size limit. Surface wind speed increases with domain size, implying that maintenance of the boundary layer winds may limit cluster size. As cluster size increases, large boundary layer temperature anomalies develop to maintain the surface pressure gradient, leading to an increase in the depth of parameterized convective heating and an increase in gross moist stability. Key Points: The sensitivity of parameterized convection to midtropospheric humidity enhances aggregation Humid clusters have a maximum scale of 3–4, 000 km, limited by the boundary layer momentum balance Larger clusters have warmer humid‐region boundary layers and deeper convective heating